Pengaruh Entrepreneurship Education Programme (EEP) pada Niat Berwirausaha Perajin Batik di Surakarta, Sragen, dan Karanganyar - Cahyono, Edi (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2014)
The purpose this study is to examine the effect of Entrepreneurship Education Programme (EEP) on the antecedents of entrepreneurial intention, and influence attitudes towards entrepreneurship and perceived behavioral control as a mediating variable. The existence of previous research is inconsistent and few studies that examines the Entrepreneurship Education Programme (EEP) on the antecedents of entrepreneurial intentions on employee motivate researchers to conduct this research. Samples taken were 120 batik employees in Surakarta, Sragen and Karanganyar. Sampling technique with purposive sampling method.The statistical methods used to test the validity, reliability, and the research hypothesis is the approach to Structural Equation Modeling (SEM). Results of this study indicate that Entrepreneurship Education Programme (EEP) have a significant effect on attitudes toward entrepreneurship, and no significant effect on the perceived behavior control and intention entrepreneurship. Attitudes towards entrepreneurship, subjective norms, and perceived behavior control have significant effect on entrepreneurial intention. Mediating influence attitudes towards entrepreneurship Entrepreneurship Education Programme (EEP) on entrepreneurial intentions.